Assessing heat exposure and its effects on farmer health, harvest yields, and nutrition: a study protocol for Burkina Faso and Kenya - Barteit, Sandra; Ouedraogo, Windpanga Aristide; Mueller, Charlotte; Zabre, Pascal; Traore, Issouf; Boudo, Valentin; Sié, Ali; Compaore, Guillaume; Ouermi, Lucienne; Munga, Stephen; Obor, David; Bunker, Aditi; et al. (Global health action, 2025)
Rising temperatures in Africa present an increasing threat to agricultural productivity and public health, particularly among subsistence farming communities reliant on rain-fed agriculture. Heat exposure can impair farmers' work capacity, disrupt harvests, and heighten health risks, especially for young children vulnerable to undernutrition. The Heat to Harvest (H2H) study investigates how environmental heat exposure influences farmers' physiological and behavioral responses, and how these in turn affect harvest yields and child nutrition. It also examines differences in labor performance and recovery between households with and without cool roof coatings, although this intervention is not the central focus. H2H is designed as a prospective cohort study nested within two Health and Demographic Surveillance Systems (HDSS) in Nouna, Burkina Faso, and Siaya, Kenya. The study integrates environmental monitoring (temperature and humidity sensors used to compute Wet Bulb Globe Temperature), biometric data (via wearables tracking heart rate, temperature, physical activity, energy expenditure, and sleep), and GPS tracking (capturing spatial mobility and labor duration). The study is embedded within a larger cluster-randomized controlled trial, facilitating comparative analysis under varying thermal conditions. Findings will provide evidence-based insights into how climate-related heat stress affects health and agricultural outcomes, supporting the development of targeted adaptation strategies to enhance resilience, health, and food security in vulnerable farming communities.
Gesehen am 01.12.2025